Перевооружение Харьковской ТЭЦ-4 путем установки новых генерирующих мощностей с целью энергосбережения - Левин, М. М.; Ковбаса, А. А.; Мамонтов, Н. И.; Кобцев, О. М.; Воеводин, Ю. Т. (НТУ "ХПИ", 2006)
Проведено аналіз стану та експлуатації діючого енергетичного устаткування Харківської ТЕЦ-4. Запропоновано основні варіанти та напрямки реконструкції ТЕЦ-4 з метою відновлення генеруючого електрообладнання та комбінованого виробітку теплової та електричної енергії задля економії палива.

The analysis of a condition and operation of the working power equipment Kharkov TPP-4 is carried out. The basic variants and directions on reconstruction TPP-4 are offered with the purpose of restoration of a generating electric equipment both combined manufacture of thermal and electrical energy with the purpose of economy of fuel.
Reequipment Kharkov TPP-4 by installation new generating capacities with the purpose energy-saving
Keywords: Харьковский тракторный завод; энергетические котлы; части высокого давления; части низкого давления; бойлер-конденсатор; электрические нагрузки